2022
DOI: 10.3389/fimmu.2022.841910
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Extracellular Vesicles in Patients with Severe and Mild Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Myalgic encephalomyelitis, or chronic fatigue syndrome (ME/CFS) is a serious disease whose cause has yet to be identified. Objective markers of the disease are also not well understood and would serve as important tools in diagnosis and management. One potential biomarker or transmitter of immune signals in ME/CFS is the extracellular vesicle (EV) compartment. These small, membrane bound particles have been shown to play a key role in intercellular signaling. Our laboratory has focused on methods of detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Of the 12 analytes measured, no significant differences among the groups were found regarding the release of MMP-2 ( Figure 3 i), myoglobin, CRP or SAA (data not shown). Furthermore, given the divergent secretion profile of serum-treated HUVECs we reproduced the experiment with patient plasma-derived extracellular vesicles (EVs) which have been postulated to play an immunomodulatory role in ME/CFS patients [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 analytes measured, no significant differences among the groups were found regarding the release of MMP-2 ( Figure 3 i), myoglobin, CRP or SAA (data not shown). Furthermore, given the divergent secretion profile of serum-treated HUVECs we reproduced the experiment with patient plasma-derived extracellular vesicles (EVs) which have been postulated to play an immunomodulatory role in ME/CFS patients [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…can adhere to the endothelial lining and play a part in the manifestation of ME/CFS symptoms, possibly by impairing oxygen and nutrient delivery to tissues [30]. More recently, platelet activity and markers have been implicated in ME/CFS, although the authors indicated a loss of significance after statistical corrections [31]. Endothelial abnormalities have also been noted [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also alluded to the notion of anomalous clot deposition on the endothelium which can impair substance exchange between blood and tissues, and subsequently give rise to ME/CFS symptoms. Bonilla and colleagues determined that extracellular vesicles from ME/CFS patients contained significantly elevated levels of the platelet marker, CD41a [ 171 ]. CD41a is a component of GPIIb/IIIa complex – the platelet receptor that binds fibrinogen and von Willebrand factor, and mediates platelet adhesion and aggregation, and clotting.…”
Section: Haematological Findingsmentioning
confidence: 99%